(untitled) (Journal of the College of Education for Women, 2021)
Abstract The study aims to know the degree of secondary school managers’ practice of servant leadership in Gaza from their teachers’ perspective. It further aims to examine whether there are any statistically significant differences at (α 0.05≥) between the means of the study sample’s members attributed to variables such as (gender, educational qualification, and years of experience). To achieve the objectives of the study, the study adopted the descriptive survey method, using a questionnaire consisting of (30) items distributed to four domains: (workers service, ethical dealing, motivation & influence, and building an organized, integrated society). Then, the questionnaire was distributed to the sample, which consisted of (262) teachers. The study has shown that the total estimation degree of the sample regarding their managers’ use of servant leadership is great at a mean of (3.94) and a relative weight equal to (78.8%). The study has further revealed that the dimension of (ethical dealing) occupied the first rank with a relative weight of (81.4%), whereas the dimension of “workers service and motivation & influence”, scored the second rank with a relative weight of (78.7%). As for the dimension of building an organized and integrated society, it took the last rank with a relative weight of (75%). It has been further noticed that there are no statistically significant differences at (α 0.05 ≥) between the average degree of the study sample in relation to the variables (gender, educational qualification, and years of experience).